2005
DOI: 10.1038/sj.ijo.0802998
|View full text |Cite
|
Sign up to set email alerts
|

Weight history from birth through childhood and youth in relation to adult lung function, in Danish juvenile obese and non-obese men

Abstract: OBJECTIVE:To investigate the associations of birth weight, body mass index (BMI) during childhood and youth, and current BMI with adult lung function. DESIGN: Population-based longitudinal study of juvenile obese and non-obese men, who were identified at draft board examination (age range: 19-27 y) and who participated in a follow-up examination in 1981-1983 (age range: 25-48 y). Birth weight, childhood weight and height measurements from 7 to 13 y of age were obtained from school health records. Current BMI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Initial longitudinal analyses, using BMI measures obtained when the subjects were aged 9, 12, or 15 years suggested a positive association between childhood BMI and adult lung function. This finding is consistent with the results of a previous study of Danish male army recruits (18) in which BMI at 7 years was positively associated with FEV 1 and FVC 19–40 years later after adjustment for adult overweight (BMI ≥25 kg/m 2 ). However, in the present study adjustment for LBM largely eliminated the positive effect of childhood BMI, suggesting that the positive association between childhood BMI and adult lung function is explained by lean mass rather than fat mass.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Initial longitudinal analyses, using BMI measures obtained when the subjects were aged 9, 12, or 15 years suggested a positive association between childhood BMI and adult lung function. This finding is consistent with the results of a previous study of Danish male army recruits (18) in which BMI at 7 years was positively associated with FEV 1 and FVC 19–40 years later after adjustment for adult overweight (BMI ≥25 kg/m 2 ). However, in the present study adjustment for LBM largely eliminated the positive effect of childhood BMI, suggesting that the positive association between childhood BMI and adult lung function is explained by lean mass rather than fat mass.…”
Section: Discussionsupporting
confidence: 92%
“…However, Bua et al . (18) found no difference in the estimates of the effect of childhood BMI on adult lung function between those identified as juvenile obese ( n = 179) and nonobese ( n = 188) males. We are not aware of any published literature of note on this issue in women.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Additionally, the investigation revealed BMI after 7 years of age had no effect on systolic blood pressure beyond that of current adult BMI [8]. Results from a study on lung function found that BMI at 7 years of age was positively associated, and that adult BMI was negatively associated, with the measures of forced expiratory volume in one second and forced vital capacity [9].…”
Section: Draftees and Obesitymentioning
confidence: 98%